PENGEMBANGAN MULTIMEDIA INTERAKTIF ARTICULATE STORYLINE 3 BERBASIS VIDEO PADA MATERI BATIK JUMPUTAN UNTUK SISWA KELAS V SDN BAWANG 2 KOTA KEDIRI - Fatmawati, Diyah (JPG: Jurnal Pendidikan Guru, 2024)
This research is motivated by the results of observations and experiences of researchers, that SBdP learning on Jumputan Batik material at SDN Bawang 2 only uses student books. As a result, the atmosphere of the class becomes boring. This can be seen from the low motivation of student learning, so that the learning outcomes are also low. In this case, teachers should be able to increase their creativity and make the best use of school facilities to create learning media that suit the needs of students. With that, researchers want to develop video-based Articulate Storyline 3 learning media which aims to create valid, practical, and effective learning media for fifth grade students at SDN Bawang 2 Kediri. In addition, by inviting students to make Jumputan Batik, researchers can find out the level of creativity of students. In developing Video-based Articulate Storyline 3 learning media in this study using the RnD (Research and Development) method with the ADDIE model. The research instruments used were observation sheets, tests, and questionnaires. The validation test in this study obtained a score of 77% for media validation and 92% for material validation. The results of the practicality of the media from the teacher’s response obtained a score of 90% and 81% for student responses. In the wide trial, students obtained an average score of 58% for the pre test and 81% for the post test. In addition, the average score of students’ skills is 83%. Based on these results, it can be stated that Video-based Articulate Storyline 3 learning media on Batik Jumputan material for class V SDN Bawang 2 Kediri is valid, practical, and effective.